Study of Financing of Capital and Current Inputs - Planning Commission (Planning Commission, 1969)
The papers on methodology, objectives, scope, sampling design, guide points, schedules and instructions thereon have been brought out in a compendium for the convenience of the officers engaged on this study. The compendium has been prepared with the joint efforts of all the officers of the PEO especially of the Agricultural Economics Division. As in the past it is hoped that this compendium will be found handy by the field officers. It is expected that the use of compendium will justify the efforts put in for its preparation.
High Yielding Varieties Design, Schedules, Etc. and Instructions